MANAGEMENT OF HOT SPRING BATHING FACILITIES IN PINANG RIVER KUANTAN SINGINGI REGENCY RIAU PROVINCE - Silviya Ningsih; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the Development of Tourism Object Facilities at Pinang River Hot Springs, Kuantan Singingi Regency, Riau Province. Main facilities, Supporting Facilities and supporting facilities. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the circumstances that occur by collecting data and information in the field. The key informants in this study are the Head of Tourism, Tourism Object Managers and Visitors. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study, it can be concluded that the conditions of the facilities available at the Sungai Pinang hot spring bath are adequate, however, there are several facilities that are not optimally maintained due to the lack of managed facilities and lack of maintenance related to cleanliness from the manager such as toilets, changing rooms and gazeboh. Keywords: Managrment. Facilities. river pinang hot springs